Analisis Kesesuaian Konsep Biologi Dalam Kartun Animasi Magic School Bus Sebagai Sumber Belajar IPA: (Analysis of the Suitability of Biological Concepts in the Magic School Bus Animated Cartoon as a Science Learning Resource) - Fakihuddin , Muhammad; Qurbaniah, Mahwar; Sunandar , Ari (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2025)
Magic School Bus is one of the animation products that can be used to improve students' skills in understanding science subject matter. The purpose of this researcher is to find out the concept of biology, the suitability of the concept with scientific literature, and biology learning materials related to the concept of biology in the animated cartoon Magic School Bus. This research is a Library Research or library research. The instruments used in this study were observation sheets, concept data cards, expert verification sheets, and research instrument validation sheets. Data analysis was carried out by looking for the biology concepts contained in the minutes of each episode along with scientific literature, as well as biology learning materials related to the concept of biology in the animated cartoon. Then the biology concepts obtained were verified by material experts first to determine whether or not the concept was appropriate. So that 83 biology concepts were found in animated cartoons and also scientific literature concepts, 2 of which were not in accordance with scientific literature. The results obtained were that the percentage of the suitability of the concept of biology in this animated cartoon with the concept of scientific literature was 97.60% with the category Very Appropriate. Biology learning materials related to the concept of biology in the animated cartoon